Key success factors of green building implementation in Malaysia construction industry / Nor Suzila Lop, Asmalia Che Ahmad and Nik Aqlima Diyana Nik Zulkipli - Nor Suzila, Lop; Asmalia, Che Ahmad; Nik Aqlima Diyana, Nik Zulkipli (2015)
Green building has become increasingly on demand and important in Malaysia. However, the implementation of the green building still has not become the interest of all groups in the construction industry. Green Buildings should be designed and operated to reduce the overall impact of the built environment on its surroundings. Therefore the aim of this research is focused on the perspective of building designers towards Green Building implementation in Malaysia construction industry. The objectives of this research are; to identify the level of awareness amongst the architects towards the implementation of green buildingand to determine the key success factors of the green building implementation in Malaysia. In order to achieve the aim and the objectives of the study, a comprehensive review of literatures and questionnaire survey were carried out. The survey was conducted on a total of 82ofarchitectfirmsinKlang Valley. Thearchitectwaschosen as the respondents to gather relevant data and information for this research. The data was analysedandestablished that most of the designers are aware of the green building implementation in Malaysia. In addition, the results concluded that providing education and training to construction practitioners on green building concept and technology, increase clients awareness and government initiatives to enhance the understanding and implementation on the green building construction are the key success factors to increase the implementation and involvement of Green Building amongst architects.